(untitled) - Jones, Stephen R. (Camden, Me., 2000)
Reading this book is as pleasant an experience as actually viewing the tall, gently waving prairie grasses and pastoral scenes that Jones (Colorado Nature Almanac, 1998) describes. Each of the 20 chapters here is devoted to a single topic or theme, such as Landmarks, Grass, Pine Lake, Tallgrass Desert, Dune Dancers, East Meets West, and Transition. All are described in fond and gentle detail, and even though there are no photos, the images are as clear as if there were. Often, the author recounts Native American legends, which he has garnered from visits and interviews and which are tied to the relevant theme, location, or local thought. An extensive bibliographic essay provides advice and sources for further reading. This book belongs in every Nebraska library, as well as in most public and academic environmental essay collections.
Keywords: Sandhills,Natural history,Prairie ecology,Sandhills ( Neb. ); Lịch sử,History; Nebraska,Sandhills,Nebraska,Sandhills